Pemberdayaan Siswi SMP Negeri 3 Gemolong Melalui Character & Communication Training (CCT) Dalam Membangun Efikasi Diri Remaja - Andriani Mei Astuti; Hani Risnawati; Insanul Firdaus (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2026)
Early adolescence is characterized by significant social and emotional development that may influence self-efficacy and adolescents’ confidence in communicating with others. An initial assessment among female students at SMP Negeri 3 Gemolong indicated that 86.0% of participants had moderate to low levels of self-efficacy. This study aimed to improve self-efficacy through Character & Communication Training (CCT) as a school-based youth empowerment approach. A pre-experimental one-group pretest-posttest design was employed involving 50 female students. The intervention consisted of self-potential identification, character strengthening, effective and assertive communication, public speaking, role-play, simulation, reflection, and peer feedback. Data were collected using a self-efficacy questionnaire and assessments of communication skills and self-confidence. Data were analyzed descriptively using frequency distributions and percentages. The proportion of participants with high self-efficacy increased from 14.0% at pretest to 54.0% at posttest, while those with low self-efficacy decreased from 30.0% to 6.0%. The proportion demonstrating good communication skills increased from 16.0% to 62.0%, while the proportion with high self-confidence increased from 12.0% to 58.0%. CCT demonstrated positive descriptive changes in self-efficacy, communication skills, and self-confidence among female students. CCT has potential as a school-based youth empowerment strategy that integrates character development with essential communication skills.